Research on the Information Security Problems in Cloud Calculation's Environment - Xia Hu; Min Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the development of technology, cloud calculation becomes a widely used technology and is regarded as the third IT revolution following the computers and the Internet. Then only after resolving its security issues, it is able to operate successfully. This paper at first introduces the concept and characteristics of cloud calculation and then elaborates the current situation of cloud calculation's security.Then it analyzes the security risks of cloud calculation. According to these risks, the solution is proposed. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3612